2008
DOI: 10.1016/j.peptides.2008.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Reduced ability of C-type natriuretic peptide (CNP) to activate natriuretic peptide receptor B (NPR-B) causes dwarfism in lbab−/− mice

Abstract: C-type natriuretic peptide (CNP) stimulates endochondrial ossification by activating the transmembrane guanylyl cyclase, natriuretic peptide receptor-B (NPR-B). Recently, a spontaneous autosomal recessive mutation that causes severe dwarfism in mice was identified. The mutant, called long bone abnormality (lbab), contains a single point mutation that converts an arginine to a glycine in a conserved coding region of the CNP gene, but how this mutation affects CNP activity has not been reported. Here, we determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 33 publications
(33 reference statements)
0
14
0
Order By: Relevance
“…Identical errors were observed in the lbab (long bone abnormality) mouse ( Fig. 2 F and H), which contains a single point mutation in the CNP gene, resulting in an exchange of an arginine that is critical for the binding of CNP to an acidic pocket in the Npr2 receptor (26)(27)(28). Consistent with the results of the DiI tracings at embryonic stages, a bifurcation failure is also found at mature stages for all sensory axons as revealed by analyzing crosses of Thy1-YFP-H (29) reporter mice with CNPdeficient mice (Fig.…”
Section: Expression Of Cnp In the Dorsal Spinal Cord During The Ingromentioning
confidence: 64%
“…Identical errors were observed in the lbab (long bone abnormality) mouse ( Fig. 2 F and H), which contains a single point mutation in the CNP gene, resulting in an exchange of an arginine that is critical for the binding of CNP to an acidic pocket in the Npr2 receptor (26)(27)(28). Consistent with the results of the DiI tracings at embryonic stages, a bifurcation failure is also found at mature stages for all sensory axons as revealed by analyzing crosses of Thy1-YFP-H (29) reporter mice with CNPdeficient mice (Fig.…”
Section: Expression Of Cnp In the Dorsal Spinal Cord During The Ingromentioning
confidence: 64%
“…Recent studies have elucidated that the impaired growth of lbab/lbab mice is caused by a hypomorphic mutation in the CNP gene; Jiao et al [11] found that its impaired growth phenotype is associated with a single point mutation in the mouse CNP gene, and we showed that this phenotype is completely recovered by CNP overexpression [12]. Yoder et al [13] characterized the mutant CNP in lbab/lbab mice and demonstrated that it is less biologically active than authentic CNP; in whole-cell cGMP elevation and membrane guanylyl cyclase assays, 30-fold to greater than 100-fold more mutant CNP is required to activate GC-B compared to authentic CNP. We also confirmed that the mutant CNP in lbab/lbab mice retains only about 10% activity to induce cyclic GMP production through GC-B compared to authentic CNP in an in vitro transfection assay using COS-7 cells [12].…”
mentioning
confidence: 55%
“…ANP binds GC-A at a stoichiometry of 1:2 and induces a rotation of the juxtamembrane region (3,4). Structural modeling studies suggest that CNP binds GC-B similarly (5,6). Natriuretic peptide binding is hypothesized to activate the receptors by relieving basal repression exerted by the kinase homology domains on the guanylyl cyclase domains (7,8).…”
Section: Natriuretic Peptides and Atp Activate And Gö6976 Inhibits Gumentioning
confidence: 99%